Fresh cassava root replacing cassava chip could enhance milk production of lactating dairy cows fed diets based on high sulfur-containing pellet - Rittikeard Prachumchai; Anusorn Cherdthong; Metha Wanapat; Sarong So; Sineenart Polyorach (My University, 2022)
Abstract The experiment objective was to assess the shifting effect from cassava chip (CC) to fresh cassava root (FC) affected feed utilization, rumen metabolism, cyanide-using bacteria, and milk quality in lactating Thai Friesian dairy cows fed diets based on high sulfur-containing pellet (PS). Four lactating Thai Friesian dairy cows of 481.5 ± 31.3 kg BW (about 4 years old were allocated with four treatments in a 4 × 4 Latin square design. The four treatments were: replacement FC for CC at 0%, 60%, 80%, and 100% dry matter (DM), respectively. Feed intakes for four diets in terms of total dry matter intake (kg/day and % BW) was linearly correlated with levels of replacement of FC (p < 0.01). Digestibilities of crude protein (CP), DM, organic matter (OM), amylase-treated neutral detergent fiber (aNDF), and acid detergent fiber (ADF) did not change with increasing levels of FC in the diet (p > 0.05). Moreover, the total bacterial counts and cyanide population utilizing bacteria cubically increased with an increase of FC replacement (p < 0.01). The effect of CC substitution with FC in the PS diet was cubically increased on blood thiocyanate concentrations (p < 0.01). In addition, the propionate (C3) concentration at 0 and 4 h post-feeding changed significantly among treatments (p < 0.01), which were linearly improved with an increasing dose of replacement FC and were highest when FC was replaced at 100%. The yield of 3.5% fat-corrected milk was high in the treatment with the replacement of FC as compared to the control (p < 0.01). The yield of fat and milk fat percentages was high (p < 0.01) in the group with the replacement of FC as compared to feed with no diet replaced. The milk thiocyanate concentration was cubically enhanced when levels of FC replacement increased (p < 0.01) and was the highest when FC was replaced at 100%. As the amount of FC replacement was raised, the somatic cell count in the milk decreased linearly (p < 0.01). In conclusion, the replacement of FC at 100% in PS could enhance the feed intake, microbial populations, total volatile fatty acid (VFA), C3 concentration, milk yield, and milk quality.
Keywords: Latin square; Neutral Detergent Fiber; Pellet; Cassava research and cyanide